1998
DOI: 10.1063/1.368946
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown and destruction of heterogeneous solid dielectrics by high voltage pulses

Abstract: Influences of reflow time and strain rate on interfacial fracture behaviors of Sn-4Ag/Cu solder joints J. Appl. Phys. 112, 064508 (2012) Early stages of mechanical deformation in indium phosphide with the zinc blende structure J. Appl. Phys. 112, 063514 (2012) Elucidating the mechanism for indentation size-effect in dielectrics Hardness, yield strength, and plastic flow in thin film metallic-glass J. Appl. Phys. 112, 053516 (2012) Development of nondestructive non-contact acousto-thermal evaluation techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 4 publications
3
66
0
Order By: Relevance
“…Though this has been identified as one of the fragmentation mechanisms with minimal environmental impacts [29][30][31][32][33], to date, this technology has however not been largely accepted by the mining and energy industry due to the huge transition that needs to be made from well-established mechanical disintegration processes [30]. Basically, the electrical disintegration of rock has limited application, mainly in the mineral liberation process, in which the generating current can be controlled.…”
Section: Electrical Disintegrationmentioning
confidence: 99%
“…Though this has been identified as one of the fragmentation mechanisms with minimal environmental impacts [29][30][31][32][33], to date, this technology has however not been largely accepted by the mining and energy industry due to the huge transition that needs to be made from well-established mechanical disintegration processes [30]. Basically, the electrical disintegration of rock has limited application, mainly in the mineral liberation process, in which the generating current can be controlled.…”
Section: Electrical Disintegrationmentioning
confidence: 99%
“…However, the fact that for very short voltage pulses, the breakdown inside the solid dielectric occurs faster than the surface flashover between the electrodes, is discovered in early sixties by Vorobiev and Vorobiev. 8 It is also shown that the most of solid dielectrics can be broken down in insulating liquids like transformer oil. In our experiments, the rising-time of high voltage pulses is only about 100 ns.…”
Section: Evidences Of Plasma Penetration Inside the Granitementioning
confidence: 99%
“…It was shown that the most of the solid dielectrics can be broken down in the insulating liquids like transformer oil, and compared to other liquid like water, the dielectric strength of transformer oil is higher. 3,8 Therefore, the transformer oil is selected as the liquid surrounding the rocks. Moreover, to enhance the electric strength around the electrode tips, two steel needles with a diameter of 1.2 mm is selected as the electrodes and the tips of the needles are placed on the interface between the transformer oil and the rock.…”
Section: Two-electrode Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of geothermal energy encounters fracturing rocks due to temperature gradients [11] and shrinkage due to cooling or drying causes cracks in basalt columns with specific spacings [12]. Dielectric breakdown of insulators [13][14][15], may also be modeled with the proposed peridynamic theory. Instead of having a conducting body with growing insulated cracks, in this case the body is an insulator in which conducting cracks grow and interact dynamically.…”
Section: Motivationmentioning
confidence: 99%